Policy Approaches to Combat Livestock Theft and Enhance Security - Stephen, Maina (International Journal of Livestock Policy, 2024)
Purpose: This study sought to analyze policy approaches to combat livestock theft and enhance security. Methodology: The study adopted a desktop research methodology. Desk research refers to secondary data or that which can be collected without fieldwork. Desk research is basically involved in collecting data from existing resources hence it is often considered a low cost technique as compared to field research, as the main cost is involved in executive's time, telephone charges and directories. Thus, the study relied on already published studies, reports and statistics. This secondary data was easily accessed through the online journals and library. Findings: The findings reveal that there exists a contextual and methodological gap relating to policy approaches to combat livestock theft and enhance security. Preliminary empirical review revealed that a multi-faceted approach is essential to effectively address livestock theft. It emphasized the importance of integrating legislative measures, technological innovations, community-based initiatives, and enhanced law enforcement efforts. Technologies like GPS tracking and RFID tags were found effective but required financial support for widespread adoption. Community involvement and education were highlighted as critical for local surveillance and theft prevention. The study also underscored the need for robust legislative frameworks and international cooperation to deter theft and ensure consistent enforcement Unique Contribution to Theory, Practice and Policy: The Routine Activity Theory, Rational Choice Theory and Situational Crime Prevention Theory may be used to anchor future studies on policy approaches on combating livestock theft and enhance security. The study concluded that an integrated approach, including advanced security technologies, community involvement, and robust legislative frameworks, was essential for effectively reducing livestock theft. It highlighted the need for financial incentives to help farmers adopt GPS tracking and RFID tags, expanded community-based initiatives like Farm Watch, and stricter penalties for theft. The study also emphasized the importance of international cooperation for standardizing livestock identification practices and supporting cross-border law enforcement efforts. These recommendations aimed to enhance livestock security, mitigate financial losses, and improve community resilience